Commercial mortgage lending as a way to long-term financing of logistics projects implemented in the format «built-to-suite» (Путеводитель предпринимателя, 2020)
This article gives a general description, and the problems of size «built-to-suite» in the current economic conditions in Russia. The mechanisms contributing to the development of logistics projects in the format «built-to-suite».